ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE (Studi Empiris pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Yusuf Mahendra; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
This research is a quantitative research that aims to analyze companys’s stock price using Altman Z-Score and also to determine the effect of the Altman Z-Score variable on stock price. The population in this study are companies that are listed in lq45 on the Indonesia Stock Exchange.The research sample was taken based on several predetermined criteria using the purposive sampling method at 45 companies over a period of 3 years from 2019 to 2021. This study uses multiple linear regression analysis to test the correlation between the independent variables and the dependent variable. The test results simultaneously prove that working capital to total asset, retained earnings to total asset, earning before interest and taxes to total asset, and book value of equity to book value total liabilities have a significant influence on the level of stock price in company lq45. While individually, this study proves that retained earning to total asset has a negative effect on the level of stock price, then this study proves that book value equity to book value total liabilities has a positive effect on the level of stock price. Meanwhile, working capital to total asset and earning before interest and taxes to total asset have no effect on the level of stock prices.